Activating health professionals as climate change and health communicators and advocates: a review - Eryn Campbell; Sri Saahitya Uppalapati; John Kotcher; Kathryn Thier; Patrick Ansah; Neha Gour; Edward Maibach (Environmental Research: Health)
Health professionals have a crucial role to play in educating the public and advocating with policymakers about the human health relevance of climate change. Here, we review 93 studies published between the years 2000–2023 on the roles health professionals can play in addressing climate change as a health issue, their knowledge of and concern about the issue, their willingness to engage with the issue, barriers they perceive to that engagement, and strategies to overcome these challenges. Overall, we found health professionals have a growing understanding of and concern about climate change’s impacts on human health and are interested in communicating about the issue and advocating for climate and health solutions. Continued efforts are needed to develop effective programming and resources to help activate, train, and support health professionals as trusted voices on the issue.